FORMULASI MOUTHWASH EKSTRAK ETANOL DAUN KESUM (Polygonum minus Huds.): bahasa indonesia - Kartikasari, Dian; Athiyah Masykuroh (Akademi Farmasi Yarsi Pontianak, 2024)
Kesum leaves (Polygonum minus Huds.) contain phenolic compounds, flavonoids, alkaloids, steroids, terpenoids, tannins, saponins and essential oils. This study aims to determine the quality of Mouthwash preparations from ethanol extract of kesum leaves (Polygonum minus Huds.) Ethanol extract of kesum leaves (Polygonum minus Huds.) obtained by extraction using maceration method with 70% ethanol solvent for 3x24 hours. Furthermore, the extract was formulated into mouthwash preparations with variations in the concentration of ethanol extract of kesum leaves, namely 0.5%, 1%, 1.5%. Quality evaluation of the moutwash preparation includes organoleptic, pH, specific gravity and viscosity. The results obtained are in the organoleptical test results in the form of a liquid, smelling a distinctive aroma of kesum leaves and menthol, 0.5% formulation R1 and R2 are brownish yellow, R3 is light yellow and in 1% formulation R1, R2, R3 are brownish yellow and in 1.5% formulation R1, R2 and R3 are solid yellow, sweet taste, slightly spicy and slightly bitter in formulas 0.5%, 1% and 1.5% in R1, R2 and R3. Clarity test on formulations 0.5%, 1%, 1.5% produced clear preparations. Viscosity test in the 0.5% formula is (2.33 ± 0.577) cPs, 1% and 1.5% formulas are (2 ± 1 cPs). Specific gravity test in the 0.5% formula is (0.86 ± 0.33), 1% formula is (1.02 ± 0.01), 1.5% (1.05 ± 0.02). The pH test in the 0.5% formula is (6.28 ± 0.20), 1% formula is (5.46 ± 0.27), 1.5% formula is (5.18 ± 0.03). So it can be concluded that the three formulas have.